Fracture of heterotopic mass in the lower limb: surgical case report and review of the literature. Issue 7 (1st July 2021) - Thompson, Joshua W; Plastow, Ricci; Rogers, Matthew; Haddad, Fares S
Abstract : Heterotopic ossification (HO) is a rare sequela of sports injuries with a predominance in young active males located within bulky muscle planes. In most cases it is self-limiting and spontaneous resolution can occur. Fractures of HO are sparsely reported within the literature. We present a rare case of a professional athlete with a recurrent fracture of mature HO within the deep fascial plane between the anterior and posterior thigh compartments. The heterotopic mass and associated fracture had restricted return to sport and thus necessitated surgical management. The athlete successfully returned to sport following surgical excision with postoperative medical therapy to inhibit recurrence.